The Influence of Content Marketing and Live Shopping on Purchasing Decisions via TikTok Shop: A Quantitative Study of @UneilHijab Consumers in Indonesia - Salsabiila, S.; Wulandari, Astri (Manunggal Halim Jaya, 2026)
This study employs a quantitative methodology to examine how content marketing and live shopping features on TikTok Shop influence purchasing decisions for Uneil Hijab products in Indonesia. A structured questionnaire was administered to 100 respondents, comprising Uneil Hijab customers on the TikTok Shop. The findings demonstrate that content marketing and live shopping significantly and positively affect consumer purchase decisions. These factors explain 71.4% of the purchase decision variance, indicating their substantial role in shaping consumer behavior. The results suggest that strategically leveraging engaging content and interactive live shopping sessions can enhance customer engagement and boost sales. This study offers actionable insights for fashion brands aiming to optimize their marketing strategies on TikTok Shop.